Investigating how to improve oral presentation skills for the second-year English major of the Department of foreign language at Hung Yen University of Technology and Education = Tìm hiểu cách cải thiện kĩ năng thuyết trình cho sinh viên chuyên Anh năm thứ hai trường Đại học Sư phạm Kĩ thuật Hưng Yên. M.A Thesis Linguistics: 60 14 10 - Nguyễn, Thị Bích Vân (2017)
The study is aimed at studying oral presentation difficulties encountered by both the secondyear major students of English and their teachers in the foreign language Department,HungYen University of Technology and Education, at finding some possible techniques for teaching oral presentations. To help the students overcome such difficulties, the research will try to-investigate the students‟ as well as teachers‟ perceptionsofwhatagood oral presentation is. -identify students‟ and teachers‟ difficulties in their learningandteaching of oral presentations. -investigate current methods the teachers use to teach presentation skills. -give suggestions for both the teachersand the students on how to deal with their difficulties in their teaching and learning of oral presentations.